Crystal structures of apo wild-type M. jannaschii tyrosyl-tRNA synthetase (TyrRS) and an engineered TyrRS specific for O-methyl-L-tyrosine - Zhang, Yan (Cold Spring Harbor Laboratory Press, 2005)
The Methanococcus jannaschii tRNA(Tyr)/TyrRS pair has been engineered to incorporate unnatural amino acids into proteins in E. coli. To reveal the structural basis for the altered specificity of mutant TyrRS for O-methyl-l-tyrosine (OMeTyr), the crystal structures for the apo wild-type and mutant M. jannaschii TyrRS were determined at 2.66 and 3.0 Å, respectively, for comparison with the published structure of TyrRS complexed with tRNA(Tyr) and substrate tyrosine. A large conformational change was found for the anticodon recognition loop 257–263 of wild-type TyrRS upon tRNA binding in order to facilitate recognition of G34 of the anticodon loop through π-stacking and hydrogen bonding interactions. Loop 133–143, which is close to the tRNA acceptor stem-binding site, also appears to be stabilized by interaction with the tRNA(Tyr). Binding of the substrate tyrosine results in subtle and cooperative movements of the side chains within the tyrosine-binding pocket. In the OMeTyr-specific mutant synthetase structure, the signature motif KMSKS loop and acceptor stem-binding loop 133–143 were surprisingly ordered in the absence of bound ATP and tRNA. The active-site mutations result in altered hydrogen bonding and steric interactions which favor binding of OMeTyr over l-tyrosine. The structure of the mutant and wild-type TyrRS now provide a basis for generating new active-site libraries to evolve synthetases specific for other unnatural amino acids.